The Impact of Using AI Chat GPT on Marketing Effectiveness: A Case Study on Instagram Marketing - Raihan Saputra; Muhammad Irwan Padli Nasution; Budi Dharma (Indonesian Journal of Economics and Management, 2023)
This study aims to investigate the impact of using AI Chat GPT on marketing effectiveness, particularly on the Instagram platform. Marketing, specifically on the Instagram platform. In obtaining structured information and effective content suggestions, increasing desired, enhancing consumer emotions and experiences, and understanding the performance of their posts in order to make informed decisions regarding content strategy. Descriptive qualitative method with virtual ethnography that looks at AIDA (Attention, Interest, Desire, Action) is used to measure the effectiveness of Instagram marketing by observing the effectiveness of Instagram marketing. The effectiveness of Instagram marketing was measured by observing the number of users who viewed, liked, visited the profile, or took a specific action after seeing the ad. The results of the study showed that marketing content created using AI Chat GPT can achieve high levels of attention and engagement among users, increasing their interest in the products or services offered by the company. These findings can help businesses improve their marketing effectiveness by using AI Chat GPT on the Instagram platform.